Nursing of a patient undergoing paravertebral nerve block for lumbar disc herniation (腰椎间盘突出症行椎旁神经阻滞镇痛1例的护理体会) - DONG Wei (董伟); SHEN Hui (申慧); WANG Cuiying (王翠英); ZHANG Xiangju (张香菊); LIU Tianhao (刘天浩); CHANG Shilei (常石磊); XIE Yingdong (解英东); SUN Lei (孙磊) (中西医结合护理)
This paper summarized the nursing management for a patient undergoing paravertebral nerve block for lumbar disc herniation (LDH). The paravertebral nerve block was effective to relieve the low back pain caused by LDH. Comprehensive nursing interventions such as preoperative evaluation and education, intraoperative nursing cooperation, postoperative observation were carried out to relieve the patient’ negative emotion and ensure treatment success. (本文总结1例腰椎间盘突出症(LDH)患者行椎旁神经阻滞镇痛的护理体会。椎旁神经阻滞治疗能有效缓解患者疼痛, 通过开展治疗前评估和宣教、治疗中护理配合、治疗后密切观察等护理干预, 减轻患者负性情绪, 确保治疗顺利完成。)